Peculiarities of training and competitive activity of sportsmen-sprinters in track and field athletics - Pavlenko, V.; Pavlenko, Y. (Journal of Physical Education and Sport, 2020)
The purpose of this study was to determine the complex motor quality in the structure of motor actions of training and competitive activity at men sprinters in athletics. Objects: 12 sportsmen of high qualification of the group of the highest sports skill took part in the research. 6 sportsmen took part in the experimental work and the control group was created out of 6 sportsmen. Methods: test trainings are aimed at variable influence of motor quality from speed development. Control and experimental groups used in training exercises that ensured speed development at intensity of 80-90% of maximum. The developed and used complex of special running exercises in the experiment was based on scientific publications, personal experience, surveys of coaches who have experience of working with national teams of the corresponding level of sports training. The experimental group used a complex of multifunctional exercises in trainings which are aimed at variable influence of motor quality, which ensured development of speed. A repeated method of performing exercises was used to develop speed capabilities. Results: using the complex of multifunctional exercises aimed at variable influence of motor quality contributed to strengthening the general potential to perform exercises at maximum rate. Efficiency of using the repeated method of performance of exercises at maximum rate on trainings was experimentally defied. The use of special running exercises on the subsoil of dynamic forces and the method of complicated conditions during speed exercises contributed to the mastery of skills in sprint, correct foot setting, position of torso and work of hands during running. It is also confirmed by the experiment that the effectiveness of exercise increases significantly if the exercise is adversarial. Using the method of complicated conditions in the performance of speed exercises contributed to the setting of the technique of performance to the correct running movements during the performance of speed work. The gradual preparation of sportsmen' musculoskeletal system for the maximum running rate contributed to the improvement of test sports indicators in speed and agility of both the experimental group and the control group. Conclusions: using the correct choice of special running exercises and method of carrying out trainings which are aimed at improvement of motor quality provided improvement of sports results. The proposed complex of preparatory special running exercises allows carrying out training classes taking into account individual opportunities and sports qualification of sportsmen.